1999
DOI: 10.1063/1.479774
|View full text |Cite
|
Sign up to set email alerts
|

Pressure dependence of the local and global dynamics of polyisoprene

Abstract: We report on the pressure dependence of the local segmental and normal modes of a type-A polymer (polyisoprene) using dielectric spectroscopy. We find that external pressure exerts a stronger influence on the dynamics of the segmental mode as compared to the longest normal mode which results in the crossing of the two modes at higher pressures. The predictions of the Rouse model are not adequate to explain the different shift factors even at elevated temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
131
3
3

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(152 citation statements)
references
References 12 publications
15
131
3
3
Order By: Relevance
“…This equivalence of the pressure-sensitivity of τ α and τ N is unusual. Previous studies of PI 12 , PLA 80 and PPG 14 found the segmental mode to be more sensitive to pressure (although from measurements over a limited range on PPG, the opposite result, ∆V α < ∆V N , was also reported 15 ). However, such results depend upon the basis for comparison.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…This equivalence of the pressure-sensitivity of τ α and τ N is unusual. Previous studies of PI 12 , PLA 80 and PPG 14 found the segmental mode to be more sensitive to pressure (although from measurements over a limited range on PPG, the opposite result, ∆V α < ∆V N , was also reported 15 ). However, such results depend upon the basis for comparison.…”
Section: Resultsmentioning
confidence: 93%
“…In Figures 8 and 9 respectively, we compare the coupling of the two modes over the same P range using published data for PPG 14 and for two different molecular weights of PI 12,81 . In each case, the slope of the curve is very close to unity, indicating that in contrast with previous conclusions, the pressure dependences of the two modes are essentially the same (i.e., ∆V α~∆ V N ), at least when compared over the same range of P. However, as discussed above, this coupling may break down very close to T g .…”
Section: Resultsmentioning
confidence: 99%
“…(9) of free volume models cannot be correct. [33], PCB54 [34], PCB42 [34], cresolphthalein-dimethylether (KDE) [8], salol [8], phenylphthaleindimethylether (PDE) [8], polypropylene oxide (PPO) [42], polymethylphenylsiloxane (PMPS) [35], o-terphenyl (OTP) [17], polyepichlorhydrin (PECh) [17], polymethyltolylsiloxane (PMTS) [36], polyvinylmethylether (PVME) [17], polyvinylacetate (PVAc) [42], polystyrene (PS) [37], PPG [38], PC [8], diglycidyl ether of bisphenol A (DGEBA) [42], 1,4-polyisoprene(PI) [39,12], poly[(phenol glycidyl ether)-co-formaldehyde] (PPGE) [42], PVAc(2) [17], polyvinylethylene (PVE) [40], 1,4-polybutadiene (PB) [17], polyethylacrylate (PEA) [37], polymethylacrylate (PMA) [17], methafluoaniline [41], PCGE [42], PMA(2) [37], polymethylmethacrylate (PMMA) [17] and polyvinylchloride (PVC) [37]. Polymer networks refer to PVE networks [43].…”
Section: Resultsmentioning
confidence: 99%
“…13,14) They investigated the dielectric behavior of PIP under in a wide range of hydrostatic pressure, up to 400 MPa, in the absence of the dilution effect.…”
Section: Neat Pressure Effectmentioning
confidence: 99%